The success strategy of forest community program in Pakpak Bharat District. Issue 1 (February 2020) - Samsuri,; Permana, J; Afifuddin, Y
Abstract: Community Forest (CF) is a state forest where the main use is to empower local community. There were 11 farmer groups in District of Pakpak Bharat that had submitted applications for CF programs. The research aimed: (1) to obtain the participation degree of forest farmer group (FFG) of CF program; (2) to determine development strategies of CF program. Analysed data used descriptive analysis, participation degree and strengthens weakness opportunity threatening (SWOT) method. The research shows that the degree of participation for dissemination and formation of forest farmer groups, monitoring and evaluation was high, meanwhile the degree of group participation in work planning and implementation of the CF program is moderate. The chosen strategy for the success of the CF program were (1) increasing the government role of Pakpak Bharat district; (2) planning for management of community forest areas is harmonized with the utilization of community forest areas for the development of timber and non-timber species; (3) implementation of local plant development programs; (4) village guidance by assistants both Field Extension Officers Local governments and Self-Extension Field Officers continue to be carried out.